2019
DOI: 10.2196/11341
|View full text |Cite
|
Sign up to set email alerts
|

Hospital in Motion, a Multidimensional Implementation Project to Improve Patients’ Physical Behavior During Hospitalization: Protocol for a Mixed-Methods Study

Abstract: Background Despite the evidence of the adverse consequences of immobility during hospitalization, patients spend most of the time in bed. Although physical activity is a modifiable factor that can prevent in-hospital functional decline, bed rest is deeply rooted in the hospital culture. To attack this, a multidimensional approach is needed. Therefore, Hospital in Motion, a multidimensional implementation project, was designed to improve physical behavior during hospitalization. Obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…The Eat Walk Engage program of Mudge et al describes an approach using multiple interventions, which demonstrated a reduced length of stay after implementation in older hospitalized patients [ 9 ]. In addition, the currently ongoing Hospital in Motion study of van Delft et al describes the usage of multiple interventions tailored to tackle the numerous described barriers perceived by health care professionals and hospitalized patients [ 29 ]. The Better By Moving study will contribute to this research by providing more insight into the effectiveness of interventions that are developed bottom-up and in cocreation with the target population and by thoroughly analyzing the process of cocreation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eat Walk Engage program of Mudge et al describes an approach using multiple interventions, which demonstrated a reduced length of stay after implementation in older hospitalized patients [ 9 ]. In addition, the currently ongoing Hospital in Motion study of van Delft et al describes the usage of multiple interventions tailored to tackle the numerous described barriers perceived by health care professionals and hospitalized patients [ 29 ]. The Better By Moving study will contribute to this research by providing more insight into the effectiveness of interventions that are developed bottom-up and in cocreation with the target population and by thoroughly analyzing the process of cocreation.…”
Section: Discussionmentioning
confidence: 99%
“…The patient surveys identify the perceived barriers and enablers to physical activity using two open-ended questions, the level of encouragement patients perceive from health care professionals and context using six questions with a 5-point scale based on the questions of van Delft et al [ 29 ], and their perceived self-efficacy in performing basic mobility activities independently using seven standardized questions with a 5-point scale based on the Short Falls Efficacy Scale-International [ 30 ]. Patients participating in the baseline cross-sectional audit will be asked to complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…For more detailed information about the design and timeline, we refer readers to our published study protocol. 26 …”
Section: Methodsmentioning
confidence: 99%
“…Eligible patients were asked in random order and inclusion stopped when 8 patients wanted to participate or when no more eligible patients were available. 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation